PENGELOLAAN KEUANGAN RUMAH TANGGA: MENINGKATKAN KESEJAHTERAAN KELUARGA DI DESA SIWAL - Desy Nur Pratiwi; Yuwita Ariessa Pravasanti; Yoga Putra Pratama (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2023)
The purpose of this PkM activity is to provide an understanding of the financial management of housewives for family welfare. This PkM activity was carried out in Siwal Village, Sukoharjo Regency, Central Java. In general, the implementation of these activities has been running smoothly and well received by the community. The results of the implementation of this community service activity show that the participants understand how to manage family finances, this is shown by the enthusiasm of the participants during the discussion. Participants are also able to compile and simulate the process of preparing finances from the total income they have and the details of expenses made by the family. Keywords: Financial management, efficiency and effectiveness